2018
DOI: 10.1002/joa3.12102
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐looped stimulation cardiac pacing for recurrent vasovagal syncope: A systematic review and meta‐analysis

Abstract: BackgroundVasovagal syncope (VVS) is defined by transient loss of consciousness with spontaneous rapid recovery. Recently, a closed‐loop stimulation pacing system (CLS) has shown superior effectiveness to conventional pacing in refractory VVS. However, systematic review and meta‐analysis has not been performed. We assessed the impact of CLS implantation and reduction in recurrent VVS events by a systematic review and a meta‐analysis.MethodsWe comprehensively searched the databases of MEDLINE and EMBASE from in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…6 www.journals.viamedica.pl/folia_cardiologica of patients in the DDD-CLS group compared to 28% (95% CI 9.7-53.5%) of patients in the DDI group (p = 0.017) [23]. In a metaanalysis that compared conventional pacing with CLS-based pacing in patients with recurrent VVS (6 studies, 224 patients), a clear superiority of CLSbased pacing was shown [24]. Similar results were obtained when CLS-based pacing was compared with RDR--based pacing (a meta-analysis of 5 studies, n = 228) [25].…”
Section: Role Of Cardiac Pacing In Vasovagal Syncopementioning
confidence: 99%
“…6 www.journals.viamedica.pl/folia_cardiologica of patients in the DDD-CLS group compared to 28% (95% CI 9.7-53.5%) of patients in the DDI group (p = 0.017) [23]. In a metaanalysis that compared conventional pacing with CLS-based pacing in patients with recurrent VVS (6 studies, 224 patients), a clear superiority of CLSbased pacing was shown [24]. Similar results were obtained when CLS-based pacing was compared with RDR--based pacing (a meta-analysis of 5 studies, n = 228) [25].…”
Section: Role Of Cardiac Pacing In Vasovagal Syncopementioning
confidence: 99%
“…Due to the principle underlying the CLS sensor, it characteristically reduces symptoms associated with syncope in patients with vasovagal syndrome. Several clinical trials have evaluated the use of CLS in patients with vasovagal reflex syncope, with a mean follow-up of 30 months, and 88% of patients experienced a reduction in symptoms associated with vasovagal syndrome after using CLS [ 102 , 103 , 104 , 105 ].…”
Section: Rate Response In Implantable Cardiac Pacemakersmentioning
confidence: 99%
“…TTT can be used to unmask NMS, and the results can predict response of cardiac pacing in NMS [ 21 , 22 ]. Asystolic tilt response shows the major role of CI reflex in NMS and predicts asystolic spontaneous syncope, and thus the response to DDD-CLS (closed loop stimulation) pacing in reducing the syncope burden and syncope recurrence [ 23 , 24 , 25 , 26 , 27 ]. It was observed that in patients with NMS, in spite of DDD-CLS stimulation, prodromal symptoms were still present.…”
Section: The Importance Of the Cardioinhibitory Reflex For Patient Selection For Pacemaker Implantationmentioning
confidence: 99%